Digital Marketing Strategy to Increase Sales of SHIBIRU MSME Products - Luhung, Binawan (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2023)
Social media is used as a digital marketing strategy by many companies. This strategy is also implemented by SHIBIRU, a MSME which is engaged in the production of natural dyes. The purpose of this study is to find a digital marketing strategy as an effort to improve product marketing performance, analyze the inhibiting and driving factors in the application of digital marketing, and find solutions to the obstacles in the application of digital marketing of SHIBIRU products. The research was conducted using qualitative methods. Data was collected through in-depth interviews with 11 informants consisting of owners and buyers of SHIBIRU. The data were coded using the NVivo 12 application. The results showed that the digital marketing strategy implemented by SHIBIRU included the initiation stage with the important elements of target audience and channel choice. The main inhibiting factor stems from the unavailability of specialized personnel in the field of digital marketing. The main driving factor comes from the existence of a fairly strong communication in the community between craftsmen who use natural dyes. The solution to overcome SHIBIRU's digital marketing constraints is to use specialized personnel with adequate and relevant capabilities to handle digital marketing.